Mitochondrial genome of Geomydoecus aurei, a pocket-gopher louse - Spradling, Theresa A. (PLoS One, 2021)
Parasitic lice demonstrate an unusual array of mitochondrial genome architectures and gene arrangements. We characterized the mitochondrial genome of Geomydoecus aurei, a chewing louse (Phthiraptera: Trichodectidae) found on pocket gophers (Rodentia: Geomyidae) using reads from both Illumina and Oxford Nanopore sequencing coupled with PCR, cloning, and Sanger sequencing to verify structure and arrangement for each chromosome. The genome consisted of 12 circular mitochondrial chromosomes ranging in size from 1,318 to 2,088 nucleotides (nt). Total genome size was 19,015 nt. All 37 genes typical of metazoans (2 rRNA genes, 22 tRNA genes, and 13 protein-coding genes) were present. An average of 26% of each chromosome was composed of non-gene sequences. Within the non-gene region of each chromosome, there was a 79-nt nucleotide sequence that was identical among chromosomes and a conserved sequence with secondary structure that was always followed by a poly-T region. We hypothesize that these regions may be important in the initiation of transcription and DNA replication, respectively. The G. aurei genome shares 8 derived gene clusters with other chewing lice of mammals, but in G. aurei, genes on several chromosomes are not contiguous.